Institutional violence and violation of the right to health: Elements to rethink the demandability of the right to health in present-day Mexico - Bellamy, Clara (2020)
The objective of the present investigation was to generate evidence on elements that may constitute obstacles in the exercise of the right to health, while documenting violations of said right and characterizing the main forms of institutional violence suffered by users of public health services.  The recommendations of the Comisión Nacional de Derechos Humanos (CNDH) (National Human Rights Commission), published in its monthly gazette between 2000 and 2016, were analyzed for cases pertaining to health.  A quantitative analysis of simple frequencies and bivariate relationships was carried out and four population profiles were established: pregnant women, non-pregnant women, men and collective cases.  Subsequently, a content analysis of the legal narrations for each group was performed and analyzed through four analytical categories: (attention) waiting time, chain of errors, obstetric violence and exclusion.  We characterize the patterns present in the violation of the right to health and debate against the arguments that support the notion that most of the errors are mainly due to infrastructure problems.  In spite of considering that infrastructure deficiencies effectively influence user attention, a finding of the investigation is that, in a great number of complaint cases presented before the CNDH, infrastructure deficiencies are not the main element, but instead, are superseded by elements related to classism, racism and sexism, perpetrated through practices of discrimination, authoritarianism and social exclusion.